Successful management of complete heart block in pregnancy - V., Rajalakshmi; Elango, Shanthi K.; P., Priyadarsene; Agnes, Betty; Karthik, Sushanthini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
This case report presents a comprehensive account of effectively managing complete heart block (CHB) in a pregnant patient with prior cardiac surgery. At 36 weeks of gestation, the team opted for an elective caesarean delivery, necessitating the insertion of a temporary pacemaker. The multidisciplinary collaboration, involving obstetricians, cardiologist, and anaesthetist, played a pivotal role in ensuring a secure delivery. The report delves into the intricacies of addressing acquired CHB during pregnancy, emphasizing the scarcity of established protocols and the need for further research in this domain. Physiological changes in pregnancy, potential complications, and pacing recommendations are discussed. The success of this case underscores the significance of meticulous planning, risk stratification, and multidisciplinary approach in managing bradycardia during high-risk pregnancies. Overall, the report provides valuable insights into navigating the complexities of acquired CHB in pregnancy, advocating for enhanced screening, early recognition, and collaborative efforts among specialists.